2011
DOI: 10.1177/1553350611411492
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative System for Transvaginal Removal of Dermoid Cyst and a Comparative Study with Laparoscopy

Abstract: The objective was to introduce a new system for transvaginal removal of ovarian cyst and to evaluate its feasibility. With a new transvaginal system, ultrasound assisted culdotomy, and laparoscopy supported cystectomy if vaginal procedure failed. We conducted a retrospective review in which 35 cases using new vaginal ovarian cystectomy were compared to 40 cases of laparoscopic cystectomy for the treatment of dermoid cyst. All cystectomies were completed without conversion to laparotomy and complications. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In recent years, transvaginal approach for the removal of benign adnexal masses [9][10][11] as well as ultrasound-guided aspiration techniques, 12 have significantly modified the treatment options for selected cases of adnexal masses. The greatest benefit of transvaginal surgery is that it results in no surgical scarring to the abdominal skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, transvaginal approach for the removal of benign adnexal masses [9][10][11] as well as ultrasound-guided aspiration techniques, 12 have significantly modified the treatment options for selected cases of adnexal masses. The greatest benefit of transvaginal surgery is that it results in no surgical scarring to the abdominal skin.…”
Section: Discussionmentioning
confidence: 99%
“…After at least 3 months, patients were evaluated concerning cosmetic satisfaction, dyspareunia and any possible negative experiences. The mean follow-up duration was 8 months (range, [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Patientsmentioning
confidence: 99%
“…We recently reported that vaginal ovarian cystectomy to treat a dermoid cyst was equivalent to laparoscopic cystectomy with respect to invasiveness (13). All transvaginal cystectomies were completed without intra-operative complications, and there were no differences in operating time, blood loss, and postoperative infection between the two procedures.…”
Section: Introductionmentioning
confidence: 96%
“…On the first page of the questionnaire, the age of the patient (in 5-year intervals), the postoperative follow-up period (in 6-month intervals), and the histology of each cyst were already entered. The questionnaire Laparoscopically supported vaginal ovarian cystectomy is a newly proposed operative approach, in which the ovarian cystectomy is initially approached transvaginally; in rare cases in which a vaginal approach is impossible due to failed culdotomy, intrapelvic adhesions, or uncontrolled bleeding, laparoscopy is used to complete the operation (10,13).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonography is widely used during surgery to visualize lesions or critical vessels lying deep within organs, including the liver, 26 prostate and kidney, 27 and heart, 28 and in neurosurgery 29 and gynecological surgery. 30 These fields benefit from surgical navigation systems that combine laparoscopic vision with computed tomography, magnetic resonance imaging, or ultrasonographic images. 31–35 However, simultaneous interlacing during surgery is currently not possible because of deformation and dislocation of organs 35 by the surgical maneuver itself and the effect of gravity.…”
Section: Discussionmentioning
confidence: 99%